Modeling the flow of casson nanofluid on a stretching sheet with heat transfer: A study of electric MHD and Darcy-Forchheimer effects - Hamzeh Taha Alkasasbeh (Partial Differential Equations in Applied Mathematics)
This article investigates the flow characteristics of Casson-type nanofluid, specifically focusing on its behavior under Darcy-Forchheimer conditions over a stretching sheet with convective boundary conditions, which have significant implications across various fields, particularly in engineering and biomedical applications. Understanding this flow is crucial due to its applications in various industrial processes, such as cooling systems, material processing, and biomedical engineering, where efficient heat transfer and fluid dynamics are essential. The study primarily examines the electric magnetohydrodynamic (MHD) flow of copper oxide suspended in water, forming a Casson nanofluid. This research is significant as it contributes to the optimization of cooling techniques and enhances the performance of materials in high-temperature applications. The transformation of the governing partial differential equations (PDE) into ordinary differential equations (ODE) allows for a more manageable analytical approach, facilitating numerical solutions through MATLAB's bvp4c function. The findings reveal that pure water exhibits a greater velocity and Nusselt number compared to the copper oxide-based Casson nanofluid. Conversely, the temperature and skin friction coefficient demonstrate an inverse relationship. These insights are essential for designing more effective thermal management systems, improving energy efficiency in manufacturing processes, and advancing technologies that rely on nanofluid dynamics.